Additions to Peroneutypa (Diatrypaceae, Xylariales): Introducing P. nayariophyti sp. nov. and new host associations of P. scoparia from northern Thailand - Afshari, Naghmeh; Farias, Antonio R. G. De; Silva, Nimali Indeewari De; Bhunjun, Chitrabhanu S.; Lumyong, Saisamorn (Phytotaxa, 2023)
Fungi are essential to forest functioning and biodiversity. This research elaborates on the study of the morphology and phylogeny of Peroneutypa species in Thailand. We introduce Peroneutypa nayariophyti as a novel saprobic species from the dead wood of Nayariophyton zizyphifolium (Malvaceae) and a new record of P. scoparia with three new host associations on Dalbergia cana, Afzelia zylocarpa (Fabaceae), and Microcos paniculata (Malvaceae) in Doi Tung National Park, Chiang Rai, Thailand. The morphology of the two taxa was compared with related taxa based on features such as ascomasta, peridium, asci, and ascospores. Their position in Peroneutypa is also supported by the phylogeny of the internal transcribed spacer (ITS) region and the β-tubulin (tub2) dataset.